Reasoning about resource-bounded multi-agent systems - Nguyen, Nguyen (2011)
The thesis presents logic-based formalisms for modelling and reasoning about resource-bounded multi-agent systems. In the field of multi-agent system, it is well-known that temporal logics such as CTL and ATL are powerful tools for reasoning about multi-agent systems. However, there is no natural way to utilise these logics for expressing and reasoning about properties of multi-agent systems where actions of agents require resources to be able to perform. This thesis extends logics including Computational Tree Logic (CTL), Coalition Logic (CL) and Alternating-time Temporal Logic (ATL) which have been used to reasoning about multi-agent systems so that the extended ones have the power to specify and to reason about properties of resource-bounded multi-agent systems. While the extension of CTL is adapted for specifying and reasoning about properties of systems of resource-bounded reasoners where the resources are explicitly memory, communication and time, the extensions of CL and ATL are generalised so that any resource-bounded multi-agent system can be modelled, specified and reasoned about. For each of the logics, we describe the range of resource-bounded multi-agent systems they can account for and axiomatisation systems for reasoning which are proved to be sound and complete. Moreover, we also study the satisfiability problem of these logics.